In Search of the Free Individual The History of the Russian-Soviet Soul - Alexievich, Svetlana (Distinguished Speakers Series, 2018)
"I love life in its living form, life that's found on the street, in human conversations, shouts, and moans." So begins this speech delivered in Russian at Cornell University by Svetlana Alexievich, winner of the 2015 Nobel Prize in Literature. In poetic language, Alexievich traces the origins of her deeply affecting blend of journalism, oral history, and creative writing. Cornell Global Perspectives is an imprint of Cornell University's Mario Einaudi Center for International Studies. The works examine critical global challenges, often from an interdisciplinary perspective, and are intended for a non-specialist audience. The Distinguished Speaker Series presents edited transcripts of talks delivered at Cornell, both in the original language and in translation.